2018
DOI: 10.1111/phpp.12420
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of methylene blue‐mediated photodynamic therapy vs intense pulsed light in the treatment of onychomycosis in the toenails

Abstract: Photodynamic therapy and IPL were effective for onychomycosis cure of any etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 47 publications
0
28
0
3
Order By: Relevance
“…The photoactivation increases the energetic level of the photosensitizer [ 132 ]. The energy consequently generated reacts with the dissolved oxygen in the treated tissue, resulting in the formation of reactive oxygen species and free radicals which are cytotoxic [ 53 , 132 , 133 ]. The fungus absorbs the photosensitizer, making it more susceptible to destruction by apoptosis or necrosis than surrounding healthy tissue [ 3 , 61 ].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The photoactivation increases the energetic level of the photosensitizer [ 132 ]. The energy consequently generated reacts with the dissolved oxygen in the treated tissue, resulting in the formation of reactive oxygen species and free radicals which are cytotoxic [ 53 , 132 , 133 ]. The fungus absorbs the photosensitizer, making it more susceptible to destruction by apoptosis or necrosis than surrounding healthy tissue [ 3 , 61 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Adverse events included mild pain, erythema, burning, edema, and blistering and were well tolerated [ 7 , 134 ]. Two recent studies, each involving 20 patients with onychomycosis also showed the effectiveness of photodynamic therapy in the treatment of onychomycosis [ 132 , 133 ]. Well-designed, large-scale, randomized studies are necessary to confirm the efficacy of photodynamic therapy in order to make formal recommendations regarding its use in the treatment of onychomycosis.…”
Section: Treatmentmentioning
confidence: 99%
“…A few clinical trials have been published on PDT, demonstrating that PDT could be a promising alternative to conventional antifungal therapy. 11,12 We conducted a short-and medium-term controlled trial to evaluate the effectiveness of PDT in the treatment of mild-to-moderate onychomycosis. In addition, a comparison between methylene blue (MB) and methyl aminolevulinate (MAL) as PSs was carried out in terms of clinical and mycological cure.…”
mentioning
confidence: 99%
“…IPL in the treatment of mild-moderate toenail onychomycosis, showing clinical improvement rates of 70% and 80%, respectively at 28 weeks from baseline 11. The fact that onychomycosis is usually not an immediate threat to their health may lead patients to delay treatment due to the high cost of antifungal medications and their potentially harmful side effects.…”
mentioning
confidence: 99%
“…Topical antifungal medications alone are a poor choice for ONM involving multiple toe nails owing to modest improvement and need for prolonged therapy. Physical therapies, especially photodynamic therapy (PDT) and laser treatment with long-pulsed Nd:YAG and/or fractional CO 2 lasers have recently been reported to provide good results in toe nail ONM when used in combination with topical and/or oral antifungals [2-4]. But high treatment cost, lack of adequate training of the healthcare provider, and patients’ reluctance for a “laser” treatment constitute important limitations of this approach.…”
Section: Introductionmentioning
confidence: 99%